Algorithm and program for earthquake prediction based on the geological, geophysical, geomorphological and seismic data - Lu*, Ngo Thi; V., Rodkin M.; Phuong, Tran Viet; Hang, Phung Thi Thu; Quang, Nguyen; Hoan, Vu Thi (Vietnam Journal of Earth Sciences, 2016)
By applying an improved method of the Earth’s crust classification, we develop an algorithm and build an earthquake prediction program using a combination of geological, geophysical, geomorphological and seismic data. This program includes a system of multiple windows with different functions, which can divide fault zones into the different segments by the maximum magnitude values Mmax. Using the constructed program, we carried out an earthquake prediction test for the Northwest Vietnam by a combination of geological, geophysical, geomorphological and seismic data. According to the received results, zoning maps of maximum earthquake prediction for the researched region has been established. The results show that the areas, capable of generating earthquakes with Mmax = 6.5 - 6.8 are primarily concentrated along some major fault zones such as Lai Chau-Dien Bien, Son La, Song Ma, Song Da, Tuan Giao or near the intersection of these fault zones. The received results show a good accordance with the actual seismotectonic characteristics of the researched region. References Bui Van Duan, Nguyen Cong Thang, Nguyen Van Vuong, Pham Dinh Nguyen, 2013. The magnitude of the largest possible earthquake in the Muong La - Bac Yen fault zone. Journal of Sciences of the Earth 35, 53-49. Cao Dinh Trieu, 1999. Probable approach for long-term earthquake prediction in Vietnam based on the regulation of epicentral distribution. Journal of Geology, Series A (251), 14-21, Hanoi (in Vietnamese). Cao Dinh Trieu, Nguyen Huu Tuyen, Thai Anh Tuan, 2006. The correlation between the structure of the Earth’s crust and seismic activities in the Northwest region of Vietnam”. Journal of Sciences of the Earth, 28, 155-164, Hanoi (in Vietnamese). Cao Dinh Trieu, Ngo Thi Lu, Cao Xuan Bach et al., 2007. Prediction of maximum earthquake occurrence in Vietnam on the basis of crustal characteristics”. Proceedings of the 5th Vietnam’s Scientific Conference on Geophysics, 159-171, Science and Technics Publishing House, Hanoi (in Vietnamese). Dang Thanh Hai, Nguyen Duc Vinh, Cao Dinh Trieu, 2002. Long-term earthquake prediction in Lai Chau-Dien Bien region on the basis of time - magnitude model. Journal of Science and Technology, 40(4), 45-53, Hanoi (in Vietnamese). Dang Thanh Hai, 2003. Study on deep structures of the Earth’s crust and seismotectonic zoning in Northern Vietnam. Physics Ph.D. Thesis, 170p, Hanoi (in Vietnamese). Grishin A.P., 2001. The statistical model for predicting the occurrence time and magnitude of the earthquake”. Journal of Volcanology and Seismology (4), 60-65, Russian Academy of Sciences, Moscow. (in Russian). Grishin A.P., N.V. Kondoskaya, L.E. Levin, L.N. Solodinov, A.L. Petrov, O.M. Petrov, 2001. “Experiment of statistical prediction in Kaspi region (occurrence time, epicenter coordinate and magnitude value of the earthquake). Geophysics in the 21th century, The 3rd Collection of Reading Materials on Geophysics, Scientific World, 149-156. Gubin I.E., 1950. The method of seismotectonic zoning. The projects of The Geophysical Center, Russian Academy of Sciences, 13. Gumbel E.J., 1958. Statistics of Extremes”. Columbia Univ. Press. Gutenberg B. and G.F. Richter, 1954. Seismicity of the Earth and associated phenomena. Princeton Univ. Press. Ngo Thi Lu, Tran Viet Phuong, 2012. About the approach to building algorithms and processes to predict earthquakes by statistical model. Journal of Sciences of the Earth, 34(4), 535-541. Ngo Thi Lu, Tran Viet Phuong, 2013. Building a new algorithm of the program for separation of forshock and aftershock groups from earthquake catalog to ensure the independence of the events. Journal of Marine Science and Technology. 3A(13), 79-85. Ngo Thi Lu (Project manager), 2011. Assessment of the seismic potential in Vietnam based on a combination of geological, geophysical and seismic data”. The international scientific cooperation between Vietnam Academy of Science and Technology and Russian Academy of Sciences under the state-level protocol (2008-2010), Final Report, 163p, Hanoi (in Vietnamese). Ngo Thi Lu (Project manager), 2013. Establishment of experimental program for short-term earthquake prediction based on the statistical model combined with tectonophysics in Vietnam and adjacent regions. The independent project of Vietnam Academy of Science and Technology, Code VAST.DL.09/11-12, 125p, Hanoi (in Vietnamese). Nguyen Hong Phuong, 1991. Probabilistic assessment of earthquake hazard in Vietnam based on seismotectonic regionalization. Tecronophysics, 198, 81-93. Nguyen Hong Phuong, 1997. Evaluation of the maximum earthquake for seismic source zones in Vietnam by a combination of probability methods. The scientific works on geology and marine geophysics (3), 48-65, Science and Technics Publishing House, Hanoi (in Vietnamese). Nguyen Hong Phuong, 2001. Probabilistic Seismic Hazard Assessment Along the Southeastern Coast of Vietnam, Natural Hazards 24, 53-74. Nguyen Hong Phuong, Pham The Truyen, 2014. Probabilistic Seismic Hazard Assessment for the South Central Vietnam. Vietnam Journal of Earth Sciences 36, 451-461. Nguyen Dinh Xuyen (Project manager), Nguyen Ngoc Thuy et al., 1996. Database of earthquake mitigation measures in Vietnam. The final report of state-level independent project, Code KT-DL 92-07, 3 volumes, Institute of Geophysics, Hanoi (in Vietnamese). Nguyen Dinh Xuyen, 2002. Earthquake and earthquake hazard level. Internal document, Institute of Geophysics, Hanoi (in Vietnamese). Nguyen Dinh Xuyen, Pham Dinh Nguyen, Pham Quang Hung, Nguyen Anh Duong, 2003. Experiment of long-term earthquake prediction based on the mechanism of foreshock activities. Journal of Sciences of the Earth, 25(3), 193-200, Hanoi (in Vietnamese). Phan Trong Trinh, Ngo Van Liem, Nguyen Van Huong, Hoang Quang Vinh, Bui Van Thom, Bui Thi Thao, Mai Thanh Tan, Nguyen Hoang, 2012. Late Quaternary tectonics and seismotectonics along the Red River fault zone, North Vietnam. Earth-Science Reviews 114(3), 224-235. Phan Trong Trinh , Hoang Quang Vinh, Nguyen Van Huong, Ngo Van Liem, 2013. Active fault segmentation and seismic hazard in Hoa-Binh reservoir, Vietnam. Cent. Eur. J. Geosci. 5(2), 223-235. Pham Van Thuc and Kijko, A., 1985. Estimation of maximum magnitude and seismic hazard in Southeast Asia and Vietnam. Acta Geophys. Pol., XXX111 (4), 377-387. Pham Van Thuc, 2007. Seismology and earthquake in Vietnam. The monographs on natural resources and environment in Vietnam, Publishing House for Science and Technology, Vietnam Academy of Science and Technology, 378p (in Vietnamese). Reisner G.I., L.I. Ioganson, M.G. Reisner, Iu.E. Baranov, 1993. Characteristic classification of the Earth’s crust and the modern geological process. Publishing House of Russian Academy of Sciences, Moscow, 210p (in Russian). Reisner G.I., L.I. Ioganson, 1996. The Extraregional Seismotectonic Method for the Assessment of Seismic Potential. Natural Hazards 14, 3-10 (Kluwer Academic Publishers, printed in the Netherlands). Tran Thi My Thanh, 2002. Assessment of seismic hazard in Vietnam and adjacent regions. Physics Ph.D. Thesis, 161 pages, Hanoi (in Vietnamese). Vu Thi Hoan, Ngo Thi Lu, M.V. Rodkin, Tran Viet Phuong, 2014. Application of the generalized extreme value distribution to study the seismicity of the Southeast Asian. Journal of Geology. Series A, 341-345. Hanoi.